2010
DOI: 10.1016/j.ydbio.2009.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Notch1 to nephron segmentation in the developing kidney is revealed in a sensitized Notch2 background and can be augmented by reducing Mint dosage

Abstract: We previously determined that Notch2, and not Notch1 was required for forming proximal nephron segments. The dominance of Notch2 may be conserved in humans, since Notch2 mutations occur in Alagille syndrome (ALGS) 2 patients, which includes renal complications. To test whether mutations in Notch1 could increase the severity of renal complications in ALGS, we inactivated conditional Notch1 and Notch2 alleles in mice using a Six2-GFP∷Cre. This BAC transgene is expressed mosaically in renal epithelial progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
71
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 41 publications
10
71
1
Order By: Relevance
“…17 Finally, when Notch2 deletion is delayed until after nephrogenesis has begun, a sensitized background forms in which the contribution of Notch1 to nephron segmentation is revealed. 13 These findings demonstrated that canonical Notch signals acting early in the RV specify the proximal nephron fates, and Notch2 contributes the lion share of this signal. However, these experiments do not address whether Notch signaling is required again in nephron differentiation, maintenance, or physiology.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…17 Finally, when Notch2 deletion is delayed until after nephrogenesis has begun, a sensitized background forms in which the contribution of Notch1 to nephron segmentation is revealed. 13 These findings demonstrated that canonical Notch signals acting early in the RV specify the proximal nephron fates, and Notch2 contributes the lion share of this signal. However, these experiments do not address whether Notch signaling is required again in nephron differentiation, maintenance, or physiology.…”
mentioning
confidence: 86%
“…Notch1, Notch2, and genes coding for their ligands Dll1 and Jag1 are all expressed by renal vesicle (RV) cells. 13,14 After ligand binding, the juxtamembrane negative regulatory region (NRR) unfolds, permitting metalloproteases to cleave Notch. Ectodomain shedding is followed by intramembrane cleavage mediated by ␥-secretase, leading to the release of the Notch intracellular domain (NICD).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 During the conversion of RV into an S-shaped structure, a middle compartment is established in a Notch-dependent manner. Whereas Notch2 is expressed throughout the RV, 38 Dll1, a ligand capable of activating Notch receptors, is restricted to the distal compartment. 32 Notch2 activation is likely to initially occur at the boundary between distal Dll1 ϩ and proximal Dll1 Ϫ segments of the RV because ligand/receptor interaction within the same cell can be inhibitory.…”
Section: Local Signaling At Compartment Boundaries Promotes Differentmentioning
confidence: 99%